When Sacred Space becomes a Heritage Place: Pilgrimage, Worship, and Tourism in Contemporary China - Shepherd, Robert J. (The international journal of religious tourism and pilgrimage, 2018)
When promoted at sites that have traditionally been religious in character, heritage tourism evokes questions of intentionality, commodification, and authenticity. In particular, tourism at such sites is alleged to flatten out local practices, cause social problems, and commercialise the sacred. In short, local cultural practices are presumed to be transformed for the worse by tourism, a presumption which implies the existence of pristine pre-tourist cultures which can serve as baseline tools for measuring the impact of this touristic degradation. In this paper I address these concerns by examining tourism at a particular Chinese religious site, recently designated as a national park and world heritage site, the Buddhist pilgrimage destination of Mount Wutai (Ch. Wutai Shan). In 1982 the Wutai area was designated one of China's first national parks and in 2009 was inscribed on UNESCO's world heritage list. In the last two decades Wutai Shan has become one of the most visited religious destinations in northern China, primarily by citizens of the People's Republic of China (PRC). According to local, provincial, and national authorities, these overwhelmingly ethnic Han Chinese visitors are tourists, not pilgrims. Although the extent to which they identify as Buddhists is unclear, religious practice is widespread among visitors. Moreover, this practice is not hidden, since the state is very much present at Wutai Shan. State heritage policies at the site are designed to protect this as a heritage space, and thus, align with broad UNESCO preservation goals, particularly spatial arrangements. However, unlike UNESCO, local, provincial, and national authorities do not view tourism as a threat to the heritage' of Wutai Shan. Instead, by eliminating (as a direct effect of UNESCO management recommendations) a vibrant informal local economy structured around pilgrimage, state officials (particularly provincial and local officials), aim to clean up' this space, spur tourism, and capture a significant share of the resulting revenues. The net result is a situation in which state policies simultaneously enable mass tourism, manage religious practice, and seek to guide visitor experiences. What remains is not a sacred place somehow ruined by tourism and / or commodification, but a quotidian religious space at which the thick happenings of Buddhism-in-practice have been curtailed but not eliminated. In short, the enactment of this sacred place remains, albeit under the careful gaze of various parts of the state.